Association of predicted basal metabolic rate and insulin resistance in a Chinese general population - Linghuan Wang; Tingting Lu; Peixin Wu; Kang Chen; Yiming Mu (BMC Endocrine Disorders)
Abstract Background Although basal metabolic rate (BMR) is involved in glucose homeostasis, existing evidence regarding its association with insulin resistance (IR) remains inconsistent across populations. This study aimed to clarify the relationship between predicted BMR and the prevalence of IR in a large, community-based Chinese population. Methods A total of 36,115 participants aged ≥ 40 years were included from the REACTION study. Individuals with cardiovascular disease, thyroid dysfunction, malignancy, or who were using glucose-, lipid-, or blood pressure-lowering medications were excluded. BMR was estimated using the Singapore equation, and participants were categorized into quartiles (Q1–Q4) based on BMR distribution. Logistic regression models were employed to assess the association between BMR and IR, defined by the homeostasis model assessment of insulin resistance (HOMA-IR). Covariates included sex, age, smoking status, alcohol consumption, glycemic and lipid profiles, liver and kidney function, and anthropometric indices. Sensitivity analyses using inverse probability weighting and restricted cubic spline regression were conducted to verify the robustness of the findings. Results This cross-sectional study demonstrated a positive association between higher predicted BMR quartiles and increased IR risk in the overall population (P < 0.05), with a stronger association observed in women (P < 0.05). A significant interaction between gender and BMR (P for interaction < 0.05) further supported a sex-specific pattern in the BMR-IR relationship. Stratified analyses revealed consistent positive association in various subgroups stratified by age, blood pressure, body mass index (BMI), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) levels (P < 0.05). This association persisted across participants with different glucose tolerance statuses, particularly among those with normal glucose tolerance and impaired glucose regulation. The association also remained significant in both premenopausal and postmenopausal women. Sensitivity analyses confirmed the stability of the results. Conclusions Predicted BMR is independently and positively associated with IR in Chinese general population, particularly in woman. The relationship demonstrated a clear dose-response pattern and remained robust across various subgroups. Monitoring BMR dynamics and targeting modifiable metabolic factors may serve as preventive strategies against IR-relate diabetes mellitus. Further longitudinal studies are warranted to validate causality.